Low-Cycle Flexural Fatigue Behavior of Concrete Beam Reinforced with Hybrid FRP-Steel Rebar - Jinkyo F. Choo; Young-Cheol Choi; Seung-Jun Kwon; Ki-Tae Park; Sung-Won Yoo (Advances in Civil Engineering)
Studies examined experimentally the flexural behavior of concrete beams reinforced with the hybrid FRP-steel rebar but very few among them evaluated their fatigue performance. In this study, the fatigue test has been performed, and an analytical model for simulating the flexural fatigue behavior of the concrete beam reinforced with the hybrid bar considering its postyielding behavior is developed. A formula relating the postyielding fatigue strain of the rebar to the number of the fatigue cycle is suggested and used in the proposed procedure. The method simulating the low-cycle behavior of the reinforced concrete beam is found to be satisfactory and can predict the number of cyclic loading to failure.